The experience of parents in providing Islamic sexual education to their children - Waliyanti, Ema; Maulida, Ni’ma Afni (Journal of Health Technology Assessment in Midwifery, 2022)
Cases of sexual violence against children are increasing this is due to the lack of sexual education from parents. This happens because they consider sexual education to be taboo and lack of experience in Islamic sexual education for children. The purpose of this study is to explore how parents experience in providing Islamic sexual education to their children. This study uses a qualitative method with a descriptive approach. This research was conducted by in-depth interviews with 11 participants, namely parents who have children aged 0-8 years in the Kalirandu sub-village determined by purposive sampling. Test the validity of the data using member check, thick description, and peer debriefing. In data analysis using software open code 4.03. This research has received an ethical permit from FKIK UMY with the number 034/EC-KEPK FKIK UMY/I/2022. This study shows that the experience of parents in providing Islamic sexual education to children starts from preparing themselves to face the role of parents to providing material on Islamic sexual health for children. Parents in giving their role are tired and confused in providing sexual education so they do some solutions and there are several factors that influence parents in providing Islamic sexual education to their children including the way parents communicate with children, the last education of parents, the negative influence of technology, The perception of sexual education in Islam is a taboo subject, a history of parental illness and the early age of parents' marriage. The experience of parents in providing Islamic sexual education to children affects the future of children, especially related to sexual deviant behavior. Therefore, parents need to prepare themselves in delivering the education so as to minimize the occurrence of risky sexual deviant behavior in children.